Double-burden of malnutrition among the indigenous peoples (Orang Asli) of Peninsular Malaysia - Wong, Chee Yen; Mohd Shariff, Zalilah; Chua, Ee Yin; Sulaiman, Norhasmah; Chin, Yit Siew; Adznam, Siti Nur ‘Asyura (BioMed Central, 2015)
Background: Double-burden of malnutrition (DBM) is an emerging public health concern among the Orang Asli (indigenous peoples) of Peninsular Malaysia. This study aimed to identify the presence of DBM at the community and household levels in Orang Asli population and its associated demographic and socio-economic factors. Methods: This cross-sectional study was conducted in 11 Orang Asli villages surrounding the Krau Wildlife Reserve, Peninsular of Malaysia from October 2011 to January 2012. Of 438 households, a total of 981 adults and 304 children who met the study criteria agreed to participate. About 160 households were further selected with pairs of children aged 3–59 months and non-pregnant mothers aged 15–55 years. Demographic and socio-economic data were obtained using interviewer-administered questionnaire while weight and height were measured using standard procedures. Double-burden of malnutrition was defined as overweight/obese mother-underweight child (OWOBM/UWC), overweight/obese mother-stunted child (OWOBM/STC) or overweight/obese mother-underweight or/and stunted child (OWOBM/UWSTC). Binary logistic regression identified the demographic and socio-economic factors associated with double-burden households. Results: About 26 % of overweight and obese adults coexisting with high proportions of underweight (49 %) and stunted (64 %) children in these Orang Asli villages. There was a higher prevalence of households with OWOBM/ UWSTC (20 %) and OWOBM/STC (19.4 %) than households with OWOBM/UWC (12.5 %). Boys (P < 0.05), older age mothers (P < 0.05), mothers with higher education (P < 0.05) and households with income per capita less than USD 29.01 (RM 97.00) (P < 0.01) were associated with higher odds of OWOBM/STC. Jah Hut (P < 0.05) and higher number of children (P < 0.05) were significantly associated with lower odds of OWOBM/UWC. Conclusions: The occurrence of double-burden of malnutrition in Orang Asli population deserves attention. Poverty reduction, access to quality diet and improved health and nutrition literacy are among strategies that could address the coexistence of DBM in this population.